Hotel on the corner of bitter and sweet : a novel - Ford, Jamie (Ballantine Books, 2009)
Set in the ethnic neighborhoods of Seattle during World War II and Japanese American internment camps of the era, this debut novel tells the heartwarming story of widower Henry Lee, his father, and his first love Keiko Okabe.